Correlation of histological grade with Estrogen, Progesterone and HER2/neu reactivity in breast cancer (Journal of Pathology of Nepal, 2019)
Background: Treatment modalities and prognosis of breast carcinoma depend largely on their hormone receptors (Estrogen and Progesterone Receptors) and HER2/neu profile. Various studies conducted within Nepal have highlighted their overall status in breast carcinomas but studies on their correlation with histological grade are few. This study aims to correlate hormone receptors and HER2/neu status with different histological grades of invasive breast carcinoma.Materials and Methods: This is a retrospective analysis of cases received at Intrepid Cancer Diagnostics, Nepal between January 2015 to December 2018 for evaluation of status of hormonal receptors and HER2/ neu on invasive breast carcinomas. Mastectomy and excisional biopsies were included for statistical correlation between hormone receptors, HER2/neu and histological grades (n=364). P-value